Uptake of the OMERACT-OARSI hip and knee osteoarthritis core outcome set: review of randomised controlled trials from 1997 to 2017 - Smith, T; Mansfield, M; Hawker, G; Hunter, D; March, L; Boers, M; Shea, B; Christensen, R; Guillemin, F; Terwee, C; Williamson, P; Roos, E; et al. (Journal of Rheumatology, 2019)
Objective: To assess the uptake of the OMERACT-OARSI (Outcome Measures in Rheumatology- Osteoarthritis Research Society International) core outcome set (COS) domains in hip and/or knee osteoarthritis (OA) trials. Methods: There were 382 trials of hip and/or knee OA identified from the ClinicalTrial.gov registry from 1997 to 2017. Frequency of COS adoption was assessed by year and per 5-yearly phases. Results: COS adoption decreased from 61% between 1997 and 2001 to 38% between 2012 and 2016. Pain (95%) and physical function (86%) were most consistently adopted. Patient’s global assessment (48%) was the principal missing domain. Conclusion: Limited adoption of the COS domains indicates that further consideration to improve uptake is required.